2021
DOI: 10.1002/cbdv.202000941
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil of Lepidium virginicum: Protective Activity on Anthracnose Disease and Preservation Effect on the Nutraceutical Content of Tamarillo Fruit (Solanum betaceum)

Abstract: The essential oil from the annual plant Lepidium virginicum L. was chemically characterized in three consecutive years (2018–2020). The essential oils were evaluated in vitro and in situ on the causal agent of anthracnose in tamarillo fruits (Solanum betaceum). The main volatile constituents were phenylacetonitrile (>60 %), linalool (>10 %), limonene (>7 %) and α‐terpineol (>5 %). The essential oil (MIC, 19–30 μg mL−1), phenylacetonitrile (MIC, 45 μg mL−1) and α‐terpineol (MIC, 73 μg mL−1) caused a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…According to Pacheco-Hernández et al [ 21 ], the essential oil from Lepidium virginicum exerted a protective effect on the conservation of carotenoids and anthocyanins of tamarillo fruit. These compounds confer the characteristic color of the pulp and pericarp of this exotic fruit [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to Pacheco-Hernández et al [ 21 ], the essential oil from Lepidium virginicum exerted a protective effect on the conservation of carotenoids and anthocyanins of tamarillo fruit. These compounds confer the characteristic color of the pulp and pericarp of this exotic fruit [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, there are few approaches describing the in situ effect of essential oils and individual volatiles to avoid fungal growth in edible fruits. Nevertheless, Pacheco-Hernández et al [10] reported promising results on the in situ antifungal activity of the essential oil from Lepidium virgnicum and its main volatiles on the proliferation of Colletotrichum acutatum in tamarillo fruit.…”
Section: In Situ Antifungal Activity Of the Essential Oil Of Peppermint And Its Major Volatilesmentioning
confidence: 99%
“…GC-FID and GC/MS analyses were done in quintuplicate using the apparatus and run conditions as recently reported. [10] Metabolite identity was assigned in accordance with mass spectrum (70 eV), with Kovats index from the NIST database, the literature and pherobase. [14,28] Co-injection of menthol, menthone, linalool and β-Caryophyllene were additionally performed in order to confirm the identity of the main volatiles.…”
Section: Gc Profiling Of the Mentha Piperita Essential Oilmentioning
confidence: 99%
See 2 more Smart Citations